Theoretical Description of the Magnetic Properties of ?3- Hydroxo Bridged Trinuclear Copper(Ii) Complexes - Venegas-Yazigi, D; Venegas-Yazigi, D (2013)
A theoretical study of the magnetic properties, using density functional theory, of a family of trinuclear ?3-OH copper(II) complexes reported in the literature is presented. The reported X-ray crystal structures of [Cu3(?3-OH)(aat)3(H2O) 3](NO3)2·H2O (HUKDUM), where aat: 3-acetylamine-1,2,4-triazole; [Cu3(?3-OH)(aaat) 3(H2SO4)(HSO4)(H2O)] (HUKDOG), where aaat: 3-acetylamine-5-amine-1,2,4-triazole; [Cu 3(?3-OH)(PhPyCNO)3(tchlphac)2] (HOHQUR), where PhPyCNO: phenyl 2-pyridyl-ketoxime and tchlphac: acid 2,4,5-trichlorophenoxyacetic; [Cu3(?3-OH)(PhPyCNO) 3(NO3)2(CH3OH)] (ILEGEM); [Cu 3(?3-OH)(pz)3(Hpz)3(ClO 4)2] (QOPJIP), where Hpz = pyrazole; [Cu 3(?3-OH)(pz)3(Hpz)(Me3CCOO) 2]â?™2Me3CCOOH (DEFSEN) and [Cu 3(?3-OH)(8-amino-4-methyl-5-azaoct-3-en-2-one) 3][CuI3] (RITXUO), were used in the calculations. The magnetic exchange constants were calculated using the broken-symmetry approach. The calculated J values are for HUKDUM J1 = -68.6 cm-1, J2 = -69.9 cm-1, J3 = -70.4 cm-1; for HUKDOG, J1 = -73.5 cm-1, J2 = -58.9 cm -1, J3 = -62.1 cm-1; for HOHQUR J1 = -128.3 cm-1, J2 = -134.1 cm-1, J3 = -120.4 cm-1; for ILEGEM J1 = -151.6 cm-1, J2 = -173.9 cm-1, J3 = -186.9 cm-1; for QOPJIP J1 = -118.3 cm-1, J2 = -106.0 cm-1, J3 = -120.6 cm-1; for DEFSEN J 1 = -74.9 cm-1, J2 = -64.0 cm-1, J3 = -57.7 cm-1 and for RITXUO J1 = -10.9 cm-1, J2 = +14.3 cm-1, J3 = -35.4 cm-1. The Kahn-Briat model was used to correlate the calculated magnetic properties with the overlap of the magnetic orbitals. Spin density surfaces show that the delocalization mechanism is predominant in all the studied compounds. [Figure not available: see fulltext.] © 2012 Springer-Verlag Berlin Heidelberg.